Дослідження чорноліських курганів в регіоні Дністровської ГАЕС - Гуцал, А.Ф. (Археологія і давня історія України, 2019)
У статті йдеться про результати досліджень двох пізньочорноліських курганів біля с. Бернашівка Могилів-Подільського району Вінницької області. Two barrows of the late stage of Chornoliska culture were explored near Bernashivka of Mohyliv-Podilskyi district of Vinnytsia region. Mound of kurgan 1 consisted of stones of the various sizes and was rifled. The largest of stones are on a peripheral position and actually restricted the mound on all sides, although the large plates were in the center where they compose something like platform. Some stones were on a periphery. Evidently the mound had a rounded shape.